Progressive Liver Disease in Patients With Ataxia Telangiectasia - Donath, Helena; Woelke, Sandra; Theis, Marius; Heß, Ursula; Knop, Viola; Herrmann, Eva; Krauskopf, Dorothea; Kieslich, Matthias; Schubert, Ralf; Zielen, Stefan (Frontiers in Pediatrics, 2019)
Ataxia telangiectasia (A-T) is a devastating multi-system disorder characterized by progressive cerebellar ataxia, immunodeficiency, genetic instability, premature ageing and growth retardation. Due to better care the patients get older than in the past and new disease entities like disturbed glucose tolerance and liver disease emerge. The objective of the present investigation is to determine the evolution of liver disease and its relation to age and neurological deterioration. The study included 67 patients aged 1 to 38 years with classical A-T. At least two measurements of liver enzymes were performed within a minimum interval of 6 months in 56 patients. The median follow-up period was 4 years (1-16 years). A total of 316 liver enzyme measurements were performed. For analysis, patients were divided into two age groups (Group 1: <12 years; group 2: > 12 years). In addition, ultrasound of the liver and Klockgether Ataxia Score (KAS) were analyzed. We found significantly higher levels of alpha-fetoprotein (AFP) (226,8 + 20.87 ng/ml vs. 565,1 ± 24.3 ng/ml, p < 0.0001), and liver enzymes like ALT (23.52 ± 0.77 IU/L vs. 87.83 ± 5.31 IU/L, p < 0.0001) in patients in group 2. In addition, we could show a significant correlation between age and AFP, GGT, and KAS. Ultrasound revealed hepatic steatosis in 11/19 (57.9%) patients in group 2. One female patient aged 37 years died due to a hepato-cellular carcinoma (HCC). Liver disease is present in the majority of older A-T patients. Structural changes, nonalcoholic fatty liver disease and fibrosis are frequent findings. Progress of liver disease is concomitant to neurological deterioration.